Design and Applications of a SO2 Surrogate in Palladium‐Catalyzed Direct Aminosulfonylation between Aryl Iodides and Amines. (17th February 2021) - Jia, Xiuwen; Kramer, Søren; Skrydstrup, Troels; Lian, Zhong
Abstract: A new SO2 surrogate is reported that is cheap, bench‐stable, and can be accessed in just two steps from bulk chemicals. Essentially complete SO2 release is achieved in 5 minutes. Eight established sulfonylation reactions proceeded smoothly by ex situ formation of SO2 by utilizing a two‐chamber system in combination with the SO2 surrogate. Furthermore, we report the first direct aminosulfonylation between aryl iodides and amines. Broad functional group tolerance is demonstrated, and the method is applicable to pharmaceutically relevant substrates, including heterocyclic substrates. Abstract : A SO2 surrogate (SOgen) is reported, which is cheap, bench‐stable, and accessible in just two steps from bulk chemicals. SOgen releases SO2 in just a few minutes when heated in the presence of a styrene. The compatibility of this gas‐releasing method with eight previously reported sulfonylation reactions was demonstrated in a two‐chamber system. Direct aminosulfonylation between aryl iodides and amines is reported.